Biologically indeterminate yet ordered promiscuous gene expression in single medullary thymic epithelial cells. (28th October 2019) - Dhalla, Fatima; Baran‐Gale, Jeanette; Maio, Stefano; Chappell, Lia; Holländer, Georg A; Ponting, Chris P
Abstract: To induce central T‐cell tolerance, medullary thymic epithelial cells (mTEC) collectively express most protein‐coding genes, thereby presenting an extensive library of tissue‐restricted antigens (TRAs). To resolve mTEC diversity and whether promiscuous gene expression (PGE) is stochastic or coordinated, we sequenced transcriptomes of 6, 894 single mTEC, enriching for 1, 795 rare cells expressing either of two TRAs, TSPAN8 or GP2. Transcriptional heterogeneity allowed partitioning of mTEC into 15 reproducible subpopulations representing distinct maturational trajectories, stages and subtypes, including novel mTEC subsets, such as chemokine‐expressing and ciliated TEC, which warrant further characterisation. Unexpectedly, 50 modules of genes were robustly defined each showing patterns of co‐expression within individual cells, which were mainly not explicable by chromosomal location, biological pathway or tissue specificity. Further, TSPAN8 + and GP2 + mTEC were randomly dispersed within thymic medullary islands. Consequently, these data support observations that PGE exhibits ordered co‐expression, although mechanisms underlying this instruction remain biologically indeterminate. Ordered co‐expression and random spatial distribution of a diverse range of TRAs likely enhance their presentation and encounter with passing thymocytes, while maintaining mTEC identity. Synopsis: Single‐cell RNA sequencing reveals transcriptional heterogeneity based on both ordered and stochastic elements that enables a dedicated cell population, medullary thymic epithelial cells (mTECs), to mirror the body's full self‐antigen complement for development of central T‐cell tolerance. mTEC are a highly heterogeneous cell population constituting distinct maturational trajectories, stages and subtypes. Several novel mTEC subsets are identified, such as chemokineexpressing and ciliated TEC. Promiscuous gene expression exhibits both ordered and stochastic elements of co‐expression. Tissue restricted genes are reproducibly co‐expressed across individual mice and within mTEC maturational stages. The mechanism underlying this order is biologically indeterminate with respect to position within the linear genome, biological pathway, or tissue specificity and tissue restricted antigens (TRAs) are spatially distributed in a random manner within the thymic medulla. Abstract : Single‐cell RNA sequencing reveals transcriptional heterogeneity based on both ordered and stochastic elements that enables a dedicated cell population to mirror the body's full self‐antigen complement for development of central T‐cell tolerance.